Switchable (pH-Driven) Aqueous Biphasic Systems formed by Ionic Liquids as Integrated Production-Separation Platforms - Ferreira, Ana M. (Green Chem, 2017)
The ability to induce reversible transitions between homogeneous solutions and biphasic systems is of paramount relevance in separation processes. In this context, pH-triggered aqueous biphasic systems composed of ionic liquids and salts are here disclosed as switchable mono/biphasic systems, and their potential application further demonstrated through an intregated aproach comprising both the production and separation of hydroxymethylfurfural from fructose.